Unveiling the needs for ethnoscience-based e-worksheets to enhance the nature of science and environmental awareness of elementary school students - Pratiwi, Wulan Octi; Sunyono, Sunyono; Rohman, Fatkhur; Firdaus, Rangga (Indonesian Journal of Science and Mathematics Education, 2024)
The growing emphasis on culturally based education highlights the need for ethnoscience-based e-worksheets to improve students' understanding of scientific concepts. This study explores the development needs of such e-worksheets using the 4D Research and Development model, specifically focusing on the define stage through descriptive data analysis. Research instruments included interviews with natural and social sciences teachers and questionnaires assessing the needs of teachers and students. The preliminary study involved 136 students and five teachers from five elementary schools in Bandar Lampung. Findings from the teachers' needs questionnaire revealed that none (100%) had integrated natural and social sciences with local Lampung culture. Likewise, 89% of students reported never experiencing such integrated learning. Furthermore, 84% of students and all (100%) teachers strongly supported the development of ethnoscience-based e-worksheets. These findings underscore the importance of integrating local wisdom into education to enhance scientific literacy, enrich learning experiences, and foster environmental awareness.